Guided Inquiry-Based Electronic Module Development on Circulation System Ma-Terial to Improve Student Learning Outcomes - Madiany Erika Purnama; Saleh Hidayat; Rusdy A. Siroj (Universitas Muhammadiyah Prof. Dr. Hamka, 2022)
Background: Industrial era 4.0 has an impact on the world of education. This affects students, where students can understand subject matter such as biology, which contains abstract concepts such as circulation system material. The teaching materials developed in this study are expected to improve student learning outcomes by integrating guided inquiry learning models. This study aimed to determine the validity, practicality, and effectiveness of guided inquiry-based electronic modules. Method: 4D model development research. Data collection by interview and questionnaire sheet. Result: The module validation of the language validator is 83%, the material is 81%, the media 81% has a good category, while the learning device validator is 96%, the learning validator is 98%, and 94% has a very good category. Practicality is taken from student responses which are divided into three stages: 81% preliminary trial, 89% quantitative trial, and 92% final trial showing a positive response. The effectiveness of this guided inquiry-based electronic module can improve student learning outcomes seen from the N-Gain score results. The control class is 0.38 with medium criteria, and the experimental class is 0.73 with high criteria. While the psychometric results of students who studied using guided inquiry-based electronic modules for three meetings, namely the first meeting 77% (good), the second meeting 91% (very good), and the third meeting 88% (very good). Conclusion: Guided inquiry-based electronic module on circulation system material has a potential effect on improving student learning outcomes